EFEKTIVITAS PENGENDALIAN INTERNAL SISTEM PENGGAJIAN PADA BADAN PUSAT STATISTIK PROVINSI DKI JAKARTA - Sabi Afansyah (2021)
This study intends to determine the effectiveness of internal controls that are applied to the payroll accounting information system at BPS DKI Jakarta Province. This research method is descriptive qualitative research. Data collection in this study begins with conducting interviews with key informants, namely the Head of the Finance Subdivision and the Head of the Personnel Subdivision along with supporting information system at BPS DKI Jakarta Province is effective in accordance with the applicable Law/PMK/regulations and also in accordance with existing documents, payroll procedures, are in accordance with practice and theory. The function, elements, and components of COSO are all fulfilled so that the effectiveness of internal control can be realized.